A Control Simulation Tool for Online Demand Calibration - Braun, Mathias; Bernard, Thomas; Piller, Olivier; Montalvo, Idel; Deuerlein, Jochen (Procedia engineering, 2015)
Developing fast calibration algorithms is an important step towards the online simulation of hydraulic water networks. The ob- jective of this paper is to report a new demand calibration approach by using algorithms from control theory. We propose a multivariable PID control where the control parameters are identified by a system identification approach and the system matrix is decoupled. In this control approach the measured flow variables are regarded as dynamic set-points. The controllers use the demand values as manipulated variables in order to control the flow variables to the measured flow. The concept was applied successfully using a small test-network.